Līzinga līguma regulējums Komerclikumā - Stankus, Kristaps (Latvijas Universitāte, 2010)
Bachelor’s paper deals with regulation of leasing agreement in Latvia’s Commercial law. Objective of study is to consider questions concerning basic principles of leasing in general and to raise understanding of current leasing regulation in Latvia. Paper also gives review of Worlds developed countries experience in leasing regulation and their legislation features in these aspects. It is important to pay attention to new concepts of legal leasing regulation, to understand the further evolution of leasing and to propose useful suggestions to improve current situation. Summing up the studies verities and coming to conclusions it could be recognized that Latvia’s strategy in building legal framework for leasing is cautious without drastic changes and novelty based on sound practice. This will help us step by step introducing needed changes to get for the best practice in legal leasing regulation. Author gives some proposals to law makers concerning Commercial law, to finalize obtained cognitions. Given proposals basically supplement already proposed draft law with additional party’s rights and duties and suggests expanding conditions for secondary leases.
Leasing Agreement Regulation in Commercial Law
Keywords: Juridiskā zinātne